2023
DOI: 10.3389/fimmu.2022.1093990
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulatory role of matrix metalloproteinases in colitis-associated cancer

Abstract: Matrix metalloproteinases (MMPs) are an important class of enzymes in the body that function through the extracellular matrix (ECM). They are involved in diverse pathophysiological processes, such as tumor invasion and metastasis, cardiovascular diseases, arthritis, periodontal disease, osteogenesis imperfecta, and diseases of the central nervous system. MMPs participate in the occurrence and development of numerous cancers and are closely related to immunity. In the present study, we review the immunomodulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 324 publications
(379 reference statements)
0
12
0
Order By: Relevance
“…Many of the genes reported here to be associated with offspring atopic disorders (see Table 2) are involved in the immune system or in inflammation ( HLA‐DRB1 , 81 HLA‐DRB5 , 82 IFNG , 83 SH2B3 , 84 AHR , 85 AHRR , 86 LRCH1 , 87 TLR7 , 88 MMP9 , 89 MMP27 , 90 and isoform GR‐P 91 ). Other genes are involved in basic biological processes with some associations to development ( HDAC4 , 92 C18orf1 , 93 KITL1 , 94 and MMP9 89 ) or atopic disorders ( PRKCA , 95 DPP10 , 96 and ORMDL3 97 ). None of these genes has been examined in animal or in vitro studies yet, as far as we know.…”
Section: Discussionmentioning
confidence: 89%
“…Many of the genes reported here to be associated with offspring atopic disorders (see Table 2) are involved in the immune system or in inflammation ( HLA‐DRB1 , 81 HLA‐DRB5 , 82 IFNG , 83 SH2B3 , 84 AHR , 85 AHRR , 86 LRCH1 , 87 TLR7 , 88 MMP9 , 89 MMP27 , 90 and isoform GR‐P 91 ). Other genes are involved in basic biological processes with some associations to development ( HDAC4 , 92 C18orf1 , 93 KITL1 , 94 and MMP9 89 ) or atopic disorders ( PRKCA , 95 DPP10 , 96 and ORMDL3 97 ). None of these genes has been examined in animal or in vitro studies yet, as far as we know.…”
Section: Discussionmentioning
confidence: 89%
“…Matrix metalloproteinase-9 (MMP-9) is a Matrix metalloproteinase that helps degrade parts of the extracellular matrix and has also been found to be involved in processes such as inflammation, cancer invasion and metastasis 41 . Luying He et al also found that MMP9 can also regulate the activity and distribution of a variety of immune cells to affect the function of the immune system, leading to a poor prognosis of cancer 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all ECM components could be degraded by matrix metalloproteinases (MMPs), a class of calcium and zinc-dependent proteolytic enzymes [ 156 ]. MMPs could be secreted by macrophages [ 157 ]. A breast cancer study revealed that CAR-147 macrophages reduced collagen deposition in tumors and enhanced T cell infiltration into tumors, leading to a suppression of human epidermal growth factor receptor 2 (HER2)-4T1 tumor growth in mice [ 158 ].…”
Section: Challenges and Strategies Of Act In Solid Tumorsmentioning
confidence: 99%